Analysis The Effect Of Work Motivation And Competence On Employee Performance (Study On Employee’s PT JCI Padang, West Sumatera) - Choirunnisa, Yusti Mauriska; Djoko Koestiono (HABITAT, 2022)
This research was conducted at PT Japfa Comfeed Indonesia Unit Padang, which is an animal feed processing company the biggest and leading in the country. The study aims to describe and analyze the effect of work motivation and competence on employee performance at PT JCI Padang.The approach to this research uses probability sampling with simple random sampling technique. The sample used in this study was staff at the junior management level which numbered 47 people. This research method uses SEM-PLS (Structural Equation Model-Partial Least Square) to see how much influence exogenous variables have on endogenous variables using WarpPLS 6.0 software. The results of this study indicate that: (1) Work motivation has a positive and highly significant effect on employee performance of 0.556, (2) Competence has a positive and highly significant effect on employee performance of 0.333. The lowest indicator value on work motivation and competence is the need for existence and attitude. Therefore the company is expected to review the salary issues received by employees and the company should provide training about problem solving solutions.